2022
DOI: 10.1136/jnnp-2022-330237
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of quantitative and longitudinal MOG antibody testing in patients with MOGAD: a multicentre retrospective study

Abstract: BackgroundIgG antibodies against myelin oligodendrocyte glycoprotein (MOG-IgG) define a subset of associated disorders (myelin oligodendrocyte glycoprotein associated disorders (MOGAD)) that can have a relapsing course. However, information on relapse predictors is scarce. The utility of retesting MOG-IgG over time and measuring their titres is uncertain. We aimed to evaluate the clinical relevance of longitudinal MOG-IgG titre measurement to predict relapses in patients with MOGAD.MethodsIn this retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Several studies found that persistent MOG-IgG seropositivity is associated with an increased likelihood of having a relapse by a factor of 2-10 7-10 particularly when the MOG-IgG titre remains high. 7,9,10 In a recent study of 116 children with MOGAD, MOG-IgG titres decreased significantly overtime in patients with a monophasic disease course compared to patients with a relapsing disease course in the majority of children. 9 This decline of MOG-IgG titres was most prominent during the first 12 months after disease onset and a seroconversion defined as a MOG-IgG titre of less than…”
Section: The Measurement Of Serum Mog Igg Titres Is Important To Asse...mentioning
confidence: 99%
“…Several studies found that persistent MOG-IgG seropositivity is associated with an increased likelihood of having a relapse by a factor of 2-10 7-10 particularly when the MOG-IgG titre remains high. 7,9,10 In a recent study of 116 children with MOGAD, MOG-IgG titres decreased significantly overtime in patients with a monophasic disease course compared to patients with a relapsing disease course in the majority of children. 9 This decline of MOG-IgG titres was most prominent during the first 12 months after disease onset and a seroconversion defined as a MOG-IgG titre of less than…”
Section: The Measurement Of Serum Mog Igg Titres Is Important To Asse...mentioning
confidence: 99%
“…High titers are needed for MOGAD diagnosis, and seronegative conversion is associated with decreased relapse risk (9). Furthermore, relapsing MOGAD patients have higher MOG-IgG titer at remission compared to monophasic MOGAD (139). Treatments such as IVIG, Plasmapheresis, or FcRn blockers target pathogenic antibodies in the blood, including MOG-IgG.…”
Section: Biomarkers and Therapeutic Mechanismsmentioning
confidence: 99%
“…3 Second, recent findings indicate a mismatch between neuroanatomical-functional mapping at the level of meta and group analyses relative to analyses conducted in individual participants. For example, Van Essen and Glasser 4 showed that a group "striplike" definition of the FFA does not align with the definition of face-selective regions on the FG in individual hemispheresa mismatch reflective of a conversation in the broader human brain mapping field between a balance of large N studies and "precision imaging" studies in individual participants. 5,6 As such, the present study by Cohen et al motivates future research with (at least) two options: there is a relationship between tuber involvement of the FFA in ASD diagnosis in individual participants, or instead, there is a relationship between a focal neuroanatomical location of the posterolateral temporal lobe and ASD diagnosis outside of face-selective regions.…”
Section: Is There An Association Between Tuber Involvement Of the Fus...mentioning
confidence: 99%
“…Even with the appropriate assay, interpretation of MOG IgG is dependent on timing of assay relative to associated neurologic symptoms. MOG IgG can be transiently positive during active MOG antibody‐associated disease when monophasic, and persistently positive MOG IgG can provide prognostic guidance on the likelihood of relapsing disease 4 …”
Section: Potential Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation